Crosstalk between Fas and S1P1 signaling via NF-kB in osteoclasts controls bone destruction in the TMJ due to rheumatoid arthritis - Islamy Rahma Hutami; Eiji Tanaka; Takashi Izawa (Elsevier, 2019)
Rheumatoid arthritis (RA) mainly affects various joints of the body, including the temporomandibular joint (TMJ), and it involves an infiltration of autoantibodies and inflammatory leukocytes into articular tissues and the synovium. Initially, the synovial lining tissue becomes engaged with several kinds of infiltrating cells, including osteoclasts, macrophages, lymphocytes, and plasma cells. Eventually, bone degradation occurs. In order to elucidate the best therapy for RA, a comprehensive study of RA pathogenesis needs to be completed. In this article, we discuss a Fas-deficient condition which develops into RA, with an emphasis on the role of sphingosine 1-phosphate (S1P)/S1P receptor 1 signaling which induces the migration of osteoclast precursor cells. We describe that Fas/S1P1 signaling via NF-κB activation in osteoclasts is a key factor in TMJ-RA severity and we discuss a strategy for blocking nuclear translocation of the p50 NF-κB subunit as a potential therapy for attenuating osteoclastogenesis. Keywords: Temporomandibular joint, Rheumatoid arthritis, Osteoclast, Fas, S1P1, NF-κB